Shear Strength of Concrete Incorporating Recycled Optimized Concrete and Glass Waste Aggregates as Sustainable Construction Materials - Sabry Fayed; Ayman El-Zohairy; Hani Salim; Ehab A. Mlybari; Rabeea W. Bazuhair; Mohamed Ghalla (Buildings)
While the development of sustainable construction materials, such as green concrete made from glass waste or recycled concrete aggregate, has been extensively researched, much of the existing work has focused narrowly on these two components. This limited scope highlights the need for further investigation to comprehensively address their drawbacks and expand the available knowledge base. Moreover, the current study uniquely emphasizes the shear response of green concrete, a critical aspect that has not been previously explored. Push-off shear samples made of green concrete, a mixture of recycled concrete, and glass waste, were built and subjected to direct shear loading testing to investigate shear response. In different proportions (0, 10, 25, 50, and 100%), fine glass aggregate is used in place of river sand. At different ratios (0, 10, 20, and 40%), coarse glass aggregate was substituted for coarse natural aggregate to form four mixtures. Additionally, recycled concrete and coarse glass aggregates were utilized instead of coarse natural aggregates. In the last group, coarse natural aggregate was substituted with recycled concrete aggregates in different proportions (0, 16, 40, and 80%). Measurements were made of the applied shear force and the sliding of the shear transfer plane during the test. The tested mixtures’ failure, shear strength, shear slip, shear stiffness, and shear stress slip correlations were examined. According to the results, all of the samples failed in the shear transfer plane. The shear strength of mixes containing 10, 25, 50, and 100% fine glass was, respectively, 12.8%, 14.7%, 29.5%, and 39% lower than the control combination without fine glass. As the amount of recycled glass and concrete materials grew, so did the shear slip at the shear transfer plane. In recent years, numerous studies have proposed formulas to predict the push-off shear strength of plain concrete, primarily using compressive strength as the key parameter—often without accounting for the influence of infill materials. The present study introduces an improved predictive model that incorporates the contents of recycled concrete aggregate, coarse glass aggregate, or fine glass aggregate as correction factors to enhance accuracy.